“Los juegos tradicionales para desarrollar la motricidad gruesa en los niños de 4 a 5 años en el centro de educación inicial teresa león de Noboa, cantón Guaranda, provincia bolívar, período 2025 - Ruiz Abarca, Anabel Cristina (2025)
The present research was carried out with the intention of verifying the impact of traditional games on the gross motor skills of boys and girls aged 4 to 5 at the "Teresa León de Noboa" Early Childhood Education Center, located in Guaranda canton, Bolívar province, in the year 2025. To this end, a playful guide was designed and implemented using traditional activities such as hopscotch, jump rope, spinning tops, among others. The research followed a cualitative -methods approach, with a descriptive and non-experimental design, characterized by structured. The results showed significant progress in skills such as coordinated running, jumping with both feet, accurate throwing and catching, as well as maintaining both dynamic and static balance. It was concluded that traditional games, in addition to enhancing gross motor skills, also encouraged active participation, fostered cooperation among peers during play, and contributed to the preservation of cultural identity.